2016
DOI: 10.1155/2016/6147345
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of FoxO1 in Granulosa Cell Apoptosis Caused by Oxidative Stress and Protective Effects of Grape Seed Procyanidin B2

Abstract: Reactive oxygen species (ROS) are closely related to the follicular granulosa cell apoptosis. Grape seed procyanidin B2 (GSPB2) has been reported to possess potent antioxidant activity. However, the GSPB2-mediated protective effects and the underlying molecular mechanisms in granulosa cell apoptosis process remain unknown. In this study, we showed for the first time that GSPB2 treatment decreased FoxO1 protein level, improved granulosa cell viability, upregulated LC3-II protein level, and reduced granulosa cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 54 publications
2
57
0
7
Order By: Relevance
“…Thus, our findings suggested that the protective effects of hawthorn extract on the OVX rats might be due to the activation of the Nrf2 signaling pathway. This result is in accordance with the results of previous studies, which suggest that physiologically active components in hawthorn such as Procyanidin B2 might act as a mechanism for lowering oxidative stress [ 65 ]. Procyanidin B2 possesses strong free radical scavenging activity and antioxidant activity [ 66 ], and it has been demonstrated that Procyanidin B2 protects human colonic cells against oxidative stress through activation of the transcription factor Nrf2 via regulation of extracellular signal-regulated kinases (ERKs) and p38 signaling [ 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our findings suggested that the protective effects of hawthorn extract on the OVX rats might be due to the activation of the Nrf2 signaling pathway. This result is in accordance with the results of previous studies, which suggest that physiologically active components in hawthorn such as Procyanidin B2 might act as a mechanism for lowering oxidative stress [ 65 ]. Procyanidin B2 possesses strong free radical scavenging activity and antioxidant activity [ 66 ], and it has been demonstrated that Procyanidin B2 protects human colonic cells against oxidative stress through activation of the transcription factor Nrf2 via regulation of extracellular signal-regulated kinases (ERKs) and p38 signaling [ 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…Accumulating evidence has supported the idea that the supplementation of edible antioxidants is an efficient measure to attenuate the oxidative stress in the ovary [ 37 , 38 ]. Lycopene is a member of carotenoid family of compounds found in tomatoes and other red fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Excess ROS level in granulosa cells results apoptosis [ 51 53 ], which in turn resulted follicular atresia and ovarian dysfunction [ 54 ]. Sevral evidences are accumulated for the effect of exogenous oxidative stress induced by H 2 O 2 resulted in higher ROS accumulation which is harmful for DNA, lipid, protein as well as mitochondria activity and integrity and subsequently lead to granulosa cell apoptosis [ 3 , 8 , 46 , 52 , 55 ]. In agreement with this, in the present study exposure of bovine granulosa cells to moderate level of H 2 O 2 resulted in higher intracellular ROS level accompanied with lower mitochondrial activity compared to untreated control (Figs 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stress induced by environment or physiology of the animals is considered as one of the important causes of impaired fertility in the dairy cattle [ 1 , 2 ]. A considerable number of evidences manifested that, various environmental and physiological insults including diseases, heat and oxidative stress could lead to abnormal growth and function of granulosa cells in ovarian follicular development [ 3 , 4 ]. Subsequently, granulosa cells apoptosis is responsible for follicular atresia [ 5 ] and subsequently oocyte and ovarian dysfunction [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%